PENGARUH TERAPI AKUPRESUR PADA TANGAN TERHADAP NYERI PERSALINAN KALA I FASE AKTIF DI PMB RATRI RESTUNI S.ST SAMARINDA - Ariyanti, Ririn; Aulia (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2019)
Pain is a natural process in labor. The response of pain is different between one and another it is influenced by factors depended in body’s resistance mechanism since labor process. The factors are age, gender, pain’s mean, attention, previous experience, coping style, family’s support, afraid, worried, personality, fatigue, culture and social. Acupressure is one of the best non-pharmacology techniques in easiest management of labor pain, cheapest, and can be done by all of people because needs only two hands in therapy implementation. The objective of this research is to identify the influence af acupressure therapy on hands to labor pain of active phase in period I. This research was queasy experiment with non-equivalent pretest-posttest design. The population of this research was inpartu woman at PMB. Ratri Restuni, S.ST Samarinda. The sampling technique used non random sampling technique; it was the sampling quota of 15 people in intervention group and 15 people in control group. Data collection was obtained by doing interview and giving acupressure. The research finding shows that there is significant differences between pain scale before and after intervention in intervention group with t-value = 11,117 and p-value 0,05, in average pain scale of intervention group before and after intervention is 68.7, it decreases to 4.37, control group is 6.80 and there is no decreasing; the average period of this is 13 minutes and then increasing again. Acupressure therapy has to be applied in giving inpartu care in period I of active phase to decrease labor pain. For next researchers, they are expected to do more research by taking other variables that can influence labor pain; which are coping, family support, and personality.